Mineral nutrition of vegetable crops LXXV - Takahashi, H.W.; Dechen, A.R.; Carmello, Q.A. de; Haag, H.P. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1987)
Cerely (Apium graveolens L. var. dulce) is not very much cultivated in Brazil, but nowadays its cultivation has been expanded because of the increasing use of it mainly by desidrated soup industries. As the countries that tradicionally cultivate cerely have present serious nutricional problems, this work was proposed with the next objectives: To examine the effects of increasing doses of calcium in the development and production. To describe the symptoms of calcium deficiency and of excess of calcium supply. To verify the differences in resistance to the blackkeart anomaly between the cultivars Cornell 6-19 and Golden Detroit. To affair these objectives a green houve experiment was carried out us which cerely plant were cultivated in nutrient solutions which had the following calcium concentrations: 0, 50, 100, 150, 200 and 300 ppm of calcium. The authors concluded: It is possible to characterize a deficiency of calcium in both cultivars. The cultivar Golden Detroit presents a greater resistance to the symptoms of calcium deficiency. The increasing of the calcium concentration in the nutrient solutions induce a decrease of Mn concentration at the plants.